(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The 1960s and 70s witnessed an increasing number of Indians immigrating to. The USA in search of the ‘American Dream’. In the process of ‘striking roots’ in an Unknown land, the first generation of Indian – Americans were conscious to maintain strong ties with their own culture, language and ’Indlanness’. As times changed, their offspring, struggled to balance their hyphenated identities. Thus giving rise to the issues of displacement, belongingness, up rootedness and cultural differences. These issues’ strongly reflect in the writings of the diaspora writers like Jhumpa Lahiri. Unaccustomed Earth is Lahiri’s third work in line. It is a poignant collection of short stories that reveals the tragedies and drama of the immigrant experience. The present paper aims to study the issue of estrangement that arises due to the conflict bf dual identities, generation gap, cultural dissimilarities and conflict of interests.